Pain control for interstitial cystitis/bladder pain syndrome patients undergoing pelvic reconstructive surgery. Issue 4 (December 2019) - Crouss, Tess; Mancenido, Briana; Rana, Neha; Jia, Xibei; Whitmore, Kristene
Introduction: Scant research exists on pain control for interstitial cystitis patients undergoing pelvic reconstructive surgery. Our aim was to compare the perioperative courses in patients with and without interstitial cystitis undergoing pelvic reconstructive surgery performed using primarily monitored anesthesia care with local anesthesia. Methods: A retrospective chart review of surgical cases performed at a single site from November 2015 to July 2018 was performed. Joint non-gynecologic cases were excluded. Data including demographics, intraoperative variables, medication requirements, and postoperative courses were abstracted. Chi-square, independent t, and Mann–Whitney U tests were used to compare interstitial cystitis with non-interstitial cystitis patients. Results: In total, 65 separate cases met inclusion criteria and were analyzed, with 57 individual subjects. Out of the 65 cases, 33 cases were performed on interstitial cystitis patients. Only 2 of the 33 interstitial cystitis patient cases required general anesthesia. Interstitial cystitis patients did not require higher concentrations of 1% lidocaine with epinephrine (average of 3.8 mg/kg) compared to patients without (2.8 mg/kg). There was no difference between groups in perioperative complications, length of recovery, or postoperative narcotic consumption. Conclusion: Perioperative outcomes and pain control do not differ in those with and without interstitial cystitis undergoing pelvic reconstructive surgery. Prolapse surgery can be safely performed on a patient population with a high proportion of chronic pelvic pain using monitored anesthesia care with local anesthesia, without increased morbidity or difficultly with perioperative pain control.